Higher classification of the Monostilifera (Nemertea: Hoplonemertea) - Kajihara, Hiroshi (Zootaxa, 2021)
The nemertean order Monostilifera consists of 594 species in 127 genera and is distributed worldwide. Within the Monostilifera, two suborders have been recognized, Cratenemertea and Eumonostilifera. Within the latter, two, unranked clade names, Oerstediina and Amphiporina, were recently proposed without formal taxonomic definition. In this article, I give morphological circumscriptions and clade definitions for Cratenemertea, Eumonostilifera, Oerstediina, Plectonemertidae, Oerstediidae, and Amphiporina. Oerstediina and Amphiporina are placed on the Linnaean rank of infraorder. Constituent genera and species for each higher taxon are tabulated. The genus Amphiporella Friedrich, 1939 is herein replaced with Germanemertes nom. nov. to avoid homonymy with the Carboniferous fossil bryozoan genus Amphiporella Girty, 1910. Loxorrhochmidae Diesing, 1862 is declared a nomen oblitum relative to Tetrastemmatidae Hubrecht, 1897, a nomen protectum under Article 23.9 of the International Code of Zoological Nomenclature. There remain 308 species of eumonostiliferans whose infraorder affiliation is uncertain due to the lack of information on vascular morphology and molecular sequence data. The suborder affiliation of the two species Cinclidonemertes mooreae Crandall, 2010 and Verrillianemertes schultzei Senz, 2001 is left uncertain.